2016
DOI: 10.1007/s11356-015-6008-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the chemical properties and swelling coefficient of alfalfa root cell walls in the presence of toluene as a toxic agent

Abstract: The influence of toluene pollution on the chemical properties and swelling coefficient of root cell walls in alfalfa (Medicago sativa L.) was investigated. Two sets of alfalfa seedlings were selected and one set was treated with 450 mg L(-1) toluene in the nutrient solution under hydroponic culture. Thirty days after treatment with toluene, alfalfa plants were harvested and the root cell walls were isolated. Fourier-transform infrared (FTIR) spectroscopy was carried out for the characterization of the root cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…4 show absorption bands at 1628, 1542, and 1240 cm −1 that were assigned to antisymmetric stretching vibrations of carboxyl, N H bending vibrations, C N stretching, and N H bending vibrations in the amide I, II, and III, respectively. 18,25 The absorption band at 1021 cm −1 was attributed to the C-OH bending vibrations in carbohydrates 30 and the bands at 1372 and 1317 cm −1 were attributed to cellulose CH 2 stretching, 31 whereas that near 1411 cm −1 was assigned to symmetric -COO − stretching. 32 There were similar functional groups on the legume and non-legume poaceae roots.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 show absorption bands at 1628, 1542, and 1240 cm −1 that were assigned to antisymmetric stretching vibrations of carboxyl, N H bending vibrations, C N stretching, and N H bending vibrations in the amide I, II, and III, respectively. 18,25 The absorption band at 1021 cm −1 was attributed to the C-OH bending vibrations in carbohydrates 30 and the bands at 1372 and 1317 cm −1 were attributed to cellulose CH 2 stretching, 31 whereas that near 1411 cm −1 was assigned to symmetric -COO − stretching. 32 There were similar functional groups on the legume and non-legume poaceae roots.…”
Section: Resultsmentioning
confidence: 99%
“…17 There are many functional groups, such as -COOH, -OH, and -H 2 PO 4 on plant roots and their dissociation produces negative charges on the root surface, which induces electrostatic adsorption of metal ions onto plant roots. [18][19][20] Numerous studies have been carried out on the electrochemical properties of cell walls and plasma membranes of plant roots, and on how they affect the uptake of nutrient elements and toxic metals. 21,22 These studies suggest that the phytotoxicity of metal ions was mainly determined by the surface charge of plant roots.…”
Section: Introductionmentioning
confidence: 99%
“…The spectra of rice root biosorbents with and without Fe plaque appeared to be similar, revealing that the influence of the DCB method on root organic material could be neglected during Fe plaque removal. The only difference in spectra between rice root with and without Fe plaque was the disappearance of absorption at 1635 cm –1 arising mainly from the C=C linkage in the aromatic ring (Sharifi et al 2016), and at 465 and 532 cm –1 arising mainly from the C–C linkage in carbohydrate, C–H linkage in aromatic ring, or the variable angle vibration of O–H (Gauthier et al 2005). The DCB method has been widely employed to remove Fe plaque from root surfaces, although this method may influence the stability of organic matter in some degree (Sakee et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The plant grown in DCM spiked soil exhibited a more significant reduction in shoot length than in manures spiked soil. Also, the root length was significantly reduced in comparison with the solvent-free control treatment (Sharifi et al 2016).…”
Section: Morphological Effects Of Dcm On Alfalfa Seedlings Developmentmentioning
confidence: 85%
“…The inhibitory effects were more pronounced with the highest dose of DCM. Sharifi et al (2016) have shown that the toluene concentration of 450 mg L À1 has caused significant detrimental effects on the root growth of alfalfa plants.…”
Section: Morphological Effects Of Dcm On Alfalfa Seedlings Developmentmentioning
confidence: 99%